Outfox eaudiobook - Brown, Sandra (2019)
From a New York Times bestselling author, an FBI agent becomes a suspected serial killer's next-door neighbor. FBI agent Drex Easton is driven by a single goal: to outmaneuver sociopath Weston Graham, who's responsible for the disappearance of eight women. But each time Drex gets close to catching him, Weston trades one persona for another and disappears again. Now, for the first time in their long game of cat and mouse, Drex might have his chance. His suspect has recently married a succesful businesswoman, Talia Shafer. Drex poses himself as their new neighbor, waiting for the right moment to strike–but his attraction to Talia threatens to compromise his mission. This is Drex's one chance to outfox his cunning nemesis before he murders again–but first he must determine whether Talia is a heartless accomplice...or the next victim.